PERAN PENDIDIKAN PANCASILA DALAM PEMBENTUKAN KARAKTER GLOBAL CITIZEN PADA SISWA KELAS V SDN NGASINAN 2 DI ERA GLOBALISASI - Bagus Ardani, Faisal; Ratnaningrum, Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze and describe the role of Pancasila Education in the formation of global citizen character in grade V students of SD Negeri Ngasinan 2 in the era of globalization. The background of this research is the gap between students' academic achievements in the subject of Pancasila Education and students' real behavior. Students also show a very limited understanding of their identity as part of a global citizen. This study uses a descriptive qualitative approach. The subjects of the study were the principal, teachers, and students of grade V of SD Negeri Ngasinan 2, Magelang Regency. Data collection techniques are carried out through observation, interviews, and documentation. Data is analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the process of forming a global citizen character through Pancasila Education is carried out with the synergy of the implementation of the Independent Curriculum, teachers' pedagogic strategies in integrating the 8 Dimensions of Graduate Profiles, contextual learning methods, and the use of Interactive Flat Panel media, in addition to refraction, the role of teachers as moral role models, and the content of the material "From Aku to Indonesia" also play an important role. The realization of the character of a global citizen can be seen in the internalization of the five dimensions of the graduate profile: faith as a moral compass, citizenship from local to global, critical reasoning as a filter in receiving information, collaboration without discrimination, and ethical communication. The main obstacles include the disconnect between school and home, exposure to unfiltered digital content, teachers' dilemmas in corrective actions, and weak synergy between schools and parents. This study concludes that Pancasila Education plays a strategic role as a moral filter that at the same time shapes national identity and the competence of global citizens.